Analisis Tingkat Pelayanan Integrasi Transportasi Berdasarkan Persepsi Pengguna di Halte Integrasi Kawasan Blok M-Sisingamangaraja, Jakarta - Kusuma Lestari, Diana (SM Institute, 2024)
The purpose of this study is to evaluate and analyze user perceptions of the performance of integrated transportation services in Jakarta. Against the backdrop of rapid urban development and high levels of community mobility, transportation is considered a crucial element in supporting urban sustainability. This research examines how the integration of transportation modes, such as Transjakarta, KRL (Commuter Line), MRT, and LRT, contributes to user satisfaction and how people perceive the quality and reliability of these services. This research uses a combined approach between qualitative and quantitative data analysis. For qualitative data analysis, data and information obtained from interviews and document collection are presented descriptively, ensuring that the results become a reasonable, systematic, and structured description of the phenomena that occur in the context of public transportation integration services. In line with that, quantitative data analysis is carried out through validity and reliability testing of questionnaire instruments before distribution. From the results of the analysis, the implementation of the transportation integration system has a lot to be improved. In the analysis of handling priority mapping using the AHP and IPA integration method to obtain a priority order of handling in improving the quality of integrated transportation service performance, it is found that of the 18 (eighteen) service attributes of the 5 (five) transportation integration variables, the results show that there are 3 (three) service attributes that are in Quadrant I (service attributes that are the top priority for improvement), 5 (five) service attributes are in Quadrant II (attributes whose performance quality must be maintained), 6 (six) service attributes are in Quadrant III (attributes that are considered less important, but the quality of performance is considered to be decreasing so that priority is low), and 4 (four) other attributes are in Quadrant IV (attributes that are considered excessive performance). In conclusion, users consider that these service attributes are very important to support user needs but currently their performance is low so it is necessary to prioritize their improvement.